Gastrointestinal symptoms in COVID-19 patients - Branković, Marija; Jovanović, Igor; Radonjić, Tijana; Pančevski, Igor; Bukurecki, Ilija; Dukić, Marija; Popadić, Višeslav; Klašnja, Slobodan; Zdravković, Marija (Vojnosanitetski pregled, 2022)
Background/Aim. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global threat and a huge problem for our community. There are so many open questions. The aim of this study was to establish the frequency of gastrointestinal (GI) symptoms in hospitalized patients with infection caused by this virus (coronavirus disease-19 – COVID-19), but also to compare if patients with GI symptoms have a higher computed tomography (CT) scan severity score of interstitial pneumonia (IP) compared to patients with COVID-19 without GI symptoms. Methods. Our database comprised 322 patients with COVID-19 who were divided into two groups, patients with and without GI symptoms. All information was taken from anamnestic data and patients’ history, followed by statistical analysis. Results. Thorax CT scans of 206 patients (63.9%) were described as bilateral IP, of which 76 CT scans (36.9%) were described by radiologists as the peak of infection. Moreover, 130 patients (40.4%) had GI symptoms, and even 58 out of 130 patients (44.6%) reported GI symptoms as the first manifestation of COVID-19 infection. The most commonly reported one was the lack of appetite (73 patients or 56.15%). Furthermore, 65 (50%) patients reported diarrhea, 25 (19.2%) patients reported nausea and vomiting, and 9 (6.9%) patients reported abdominal pain. In addition, among patients with bilateral IP and GI tract symptoms, 31 (40.79%) of them did not have a higher CT scan severity score at the peak of the disease compared to the patients without GI symptoms (45 of them or 59.2%), (p = 0.704). Conclusion. GI symptoms often are the first manifestation of COVID-19. Therefore, every patient with newly formed digestive tract symptoms should be tested for COVID-19. On the other hand, GI symptoms do not indicate COVID-19 patients will have a severe form of IP.